Prognostic Significance of SUVmax Combined With Lactate Dehydrogenase in Advanced Lung Cancer Patients Treated With Immune Checkpoint Inhibitor Plus Chemotherapy: A Retrospective Study - Ke, Linping; Wang, Lu; Yu, Jinming; Meng, Xue (Frontiers in Oncology, 2021)
Purpose This research aims to investigate the predictive capacity of PET/CT quantitative parameters combined with haematological parameters in advanced lung cancer patients treated with immune checkpoint inhibitor (ICI) plus chemotherapy. Methods A total of 120 patients who underwent 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) were enrolled before therapy. The following parameters were calculated: the maximum, mean, and peak standardized uptake value (SUVmax, SUVmean, and SUVpeak, respectively); total tumour volume (MTV) and total lesion glycolysis (TLG); and whole-body metabolic values (MTVwb, TLGwb, SUVmeanwb, and SUVmaxwb). Lactate dehydrogenase (LDH) levels, absolute neutrophil count, absolute platelet count, albumin levels and derived neutrophil to lymphocyte ratio (dNLR) were also computed. The associations between the variables and therapy outcome (evaluated by iRECIST) were analyzed. Results Based on iRECIST, 32 of 120 patients showed iPD, 43 iSD, 36 iPR and 9 iCR. Multivariate analysis found that SUVmax, MTVwb, LDH and absolute platelet count were associated with treatment response (P =0.015, P =0.005, P <0.001 and P =0.015, respectively). Kaplan-Meier survival analyses showed that SUVmax ≥11.42 and LDH ≥245 U/L were associated with shorter OS (P = 0.001 and P = 0.004, respectively). Multivariate Cox regression revealed that SUVmax and LDH alone were not correlated with survival prognosis (p>0.05), but the combination of SUVmax and LDH was independently associated with OS (P=0.015, P=0.001, respectively). The median survival time (MST) for the low (LDH<245 and SUVmax<11.42), intermediate(LDH<245 or SUVmax<11.42), and high(SUVmax≥11.42 and LDH≥245) groups was 24.10 months (95% CI: 19.43 to 28.77), 17.41 months (95% CI: 15.83 to 18.99), and 13.76 months (95% CI: 12.51 to 15.02), respectively. Conclusion This study identified that SUVmax plus LDH correlated with the survival outcome in patients with advanced lung cancer receiving PD-1/PD-L1 blockade plus chemotherapy.